Having fun with van – a Nanosyntactic take on syncretism - Pretorius, Erin (Stellenbosch Papers in Linguistics Plus, 2014)
Syncretism is the phenomenon where one (phonological) form is able to spell out more than one (grammatical) function. The P(repositional) element van (“from/of”) in Afrikaans represents an instance of syncretism: it is able to spell out many different functions including spatial, possessive and partitive functions. Any theoretical framework seeking to account for how form relates to function ought to provide an account of this phenomenon. Within the broad minimalist approach, Nanosyntax (NS) has yielded the most systematic and explicit accounts of syncretism (cf. e.g. Starke 2009; Caha 2006, 2009). This paper offers a nanosyntactic characterisation of the Afrikaans P element van, focusing specifically on its behaviour in Afrikaans partitive constructions and offering a tentative analysis to account for the seemingly irregular behaviour displayed by van in these constructions. The analysis is based on a modified syntactic decomposition of “the genitive zone” proposed by Caha (2009). The presence of an additional node, Specific (SPF), is argued for in the lowest layer of the structure that is encoded on the lexical entry for van. One merit of the proposed analysis is that it takes into account how van interacts with other word-level elements in the phrase.